Benefit of Swimming Access to Behaviour, Body and Plumage Condition and Heat Stress Effect of Local Ducks - Suswoyo , I.; Ismoyowati; Sulistyawan, I.H. (International Journal of Poultry Science, 2014)
A study has been conducted with purposes to compare behaviour, body and plumage condition of local ducks kept in commercial farms with and without access for swimming and to assess whether the access can help the ducks to reduce heat stress effect. Twenty eight duck farms were used as respondents, each 14 came from wet and dry system. This study involved 13,820 ducks in total. Data collected were duck behaviour i.e. panting, foraging, preening, bathing and swimming. The behaviours were recorded 5 times a day i.e. 6 am, 9 am, 12 am, 3 pm and 6 pm; body condition with scores of 1 (the whole body was clean); 2 (dirt on shank); 3 (dirt on shank and thigh); 4 (dirt on shank, thigh and chest); 5 (dirt on shank, thigh, chest and wings); 6 (dirt on the whole body); body temperature. Fifteen ducks from each farms were measured their body condition and rectal temperature; farm condition. Hen day production was used to calculate egg production. Data obtained analyzed using description technique analysis and student t test. The results indicated that wet system provided better condition for the ducks although egg production between the two systems were not significantly different.